DETERMINATION OF TRANSPORT PROPERTIES OF IONS COPPER AND NICKEL IN A MEMBRANE OF CATIÓNICO EXCHANGE - Zuta, Leví (2020)
The objective of this research was to study the transport properties of copper and nickel through the fumasep FKB-PK-130 cation exchange membrane using chronopotentiometry. The membrane’s conductive area was calculated in an aqueous solution of KCl 0.025 M, obtaining an value of 0.904, corresponding to a homogenous ion exchange membrane. The transport numbers of copper and nickel ions in the cation exchange membrane were measured as 0.966 and 0.923, respectively.